NETRALITAS KORPORAT DAN BIROKRASI INOVATIF DI INDONESIA - Syafuan Rozi (Jurnal Manajemen Kepegawaian, 2009)
This article will telling us any alternatives about how Indonesian bureaucracy should be reforming and transforming its structure and values into new paradigm, culture and structure. The key words are how they can change to be a political neutrality institution and competence person, they should have good training to build clear vision as entrepreneur corporate and ascetic spiritual institution when they serving all of citizens and states. The conclusion of this article are the explanation about how any stakeholder in Indonesia should make planning of bureaucracy model of transformation and applicable implementation to achieve good bureaucracy, promoting state capacity and welfares people issues should be managed now and the future.